Pembuatan Membran Ultrafiltrasi Selulosa Asetat Untuk Pengolahan Limbah Cair Mal - Ewith Riska Rachma; Jhon Armedi Pinem; Idral Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Ultrafiltration membrane is a membrane that resist colloids, particles, microorganisms such as bacteria and viruses or macromolecules that are 1 -100 nm in size. Membrane synthesis was using cellulose acetate material with phase inversion method. The purpose of this research were to make membranes of cellulose acetate for waste water treatment mall with 12.5%, 15%, 17.5%, and 20% by weight of cellulose acetate, operating pressure of 2, 3, and 4 bars. This research produced porous membrane and it had asymmetric structure.Key words : asymmetric, mall, porous membrane, rejecton , and ultrafiltration